CLOUD MANUFACTURING: IDENTIFICATIONS AND PRIORITIZATION OF OPPORTUNITIES USING AHP - Mohneesh Kumar SHARMA (Scientific Journal of Silesian University of Technology. Series Transport)
The origin of a cost-efficient, service-oriented, customer-centric, manufacturing system called cloud manufacturing has evolved due to advancements in cyber systems and the availability of internet facilities worldwide. However, there is a significant number of opportunities before the adoption of cloud manufacturing. Through literature survey, expert opinions from academicians and industrialists, various opportunities, namely, pay-as-use, scalability, cost efficiency, flexibility, autonomy, low-risk backup and recovery, low startup cost and location independence associated with the espousal of cloud manufacturing are identified. Further, the Analytic Hierarchy Process (AHP) model is applied to find the weights and prioritize these opportunities, thereby finding the significant key opportunities. Moreover, the consistency ratio is calculated for the accuracy and consistency of the results. As the obtained value of consistency ratio is less than .1, it shows that the result obtained is consistent and accurate. The managerial implication of these outcomes is that the results would indirectly help entrepreneurs in the adoption of cloud manufacturing.